Enhanced photocatalytic and antifungal properties of Sr-doped PbS nanopowders. (23rd February 2018) - Suganya, M.; Anitha, S.; Prabha, D.; Balamurugan, S.; Srivind, J.; Balu, A. R.
Abstract: Sr-doped PbS (PbS:Sr) nanopowders were synthesised by a cost-effective chemical method with 0, 5, 10 and 15 wt.% Sr doping concentrations. The structural, morphological, photocatalytic and antifungal properties of the synthesised samples were studied and the results obtained are reported in this paper. The XRD patterns confirm that both the undoped and doped samples exhibit cubic crystal structure with a strong (2 0 0) preferential growth. Nanosized grains are evinced from the SEM and TEM images. EDX spectra confirm the presence of Sr in the doped samples. FTIR studies confirm the presence of band related to PbS at 618 cm −1 . Photodegradation efficiency of pure PbS against the degradation of methyl orange (MO) increases with Sr doping. PbS:Sr nanopowders show enhanced antifungal properties against A. terreus fungus. Among the doped samples, the 10 wt.% Sr-doped sample exhibit better photocatalytic and antifungal properties.